Non-purified commercial multiwalled carbon nanotubes supported on electrospun polyacrylonitrile@polypyrrole nanofibers as photocatalysts for water decontamination - Capilli, Gabriele (2021)
We present a photoactive composite material for water decontamination consisting of non-purified commercial multiwalled carbon nanotubes (CNT(NP)s) supported on an electrospun polymeric mat made of core–sheath polyacrylonitrile–polypyrrole nanofibers. This is the first system that specifically exploits the superior photocatalytic activity of CNT(NP)s compared with the purified carbon nanotubes usually employed. A CNT(NP) still contains the catalytic metal oxide nanoparticles (NPs) used for its synthesis, embedded in the nanotube structure. Under UV-visible irradiation, these NPs generate highly reactive ˙OH radicals capable of degrading the organic molecules adsorbed on the nanotube. Photocatalytic tests on the composite material show that CNT(NP)s act mostly as a source of photogenerated charge carriers. The adsorption of target substrates occurs preferentially onto the polypyrrole sheath, which shuttles the reactive carriers from CNT(NP)s to the substrates. In addition, UV-visible irradiation of semiconducting polypyrrole generates radical species that directly react with the adsorbed substrates. All synthetic procedures reported are scalable and sustainable. This mechanically resistant and flexible composite overcomes one of the weakest aspects of water treatments that employ suspended nanocatalysts, namely the expensive and poorly scalable recovery of the catalyst through nanofiltration. All these features are required for large-scale photocatalytic treatments of polluted water.